Pengaruh Jus Wortel terhadap Nyeri Haid (Dismenore) pada Siswi di SMAN 1 Trimurjo - Adistya Amareta; Enny Yuliaswati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Dysmenorrhea, or menstrual pain, is a common gynecological problem among adolescent girls and often interferes with their daily activities, school performance, and overall quality of life. Conventional pharmacological treatments such as nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used but may cause side effects with long-term consumption. Therefore, safe and natural alternatives are needed to manage menstrual pain effectively. Carrot juice, which is rich in beta-carotene, vitamin E, and other antioxidants, has been reported to possess anti-inflammatory and analgesic properties that could potentially reduce the severity of dysmenorrhea. This study aimed to determine the effect of carrot juice on reducing menstrual pain in female students at SMAN 1 Trimurjo. A pre-experimental study with a one-group pretest–posttest design was conducted involving 27 students who experienced dysmenorrhea. Pain intensity was assessed before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon signed-rank test. The results showed that before the intervention, the majority of respondents (85.2%) reported moderate pain, while after consuming carrot juice, 92.6% reported mild pain and 7.4% reported no pain. Statistical analysis revealed a significant difference in pain levels before and after the intervention (p = 0.000, p < 0.05). These findings indicate that carrot juice is effective in reducing dysmenorrhea intensity among adolescent girls. As a safe, affordable, and easy-to-implement non-pharmacological therapy, carrot juice has the potential to be recommended as a complementary approach to menstrual pain management, especially for adolescents who seek natural remedies. Further research with larger samples and control groups is recommended to strengthen the evidence and explore the long-term benefits of carrot juice in menstrual health.